2014
DOI: 10.1007/s00216-014-7728-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of β-methylphenethylamine, a novel doping substance, by means of UPLC/MS/MS

Abstract: Novel substances of expected doping activity are constantly introduced to the market. β-Methylphenethylamine (BMPEA) is classified as a doping agent by the World Anti-Doping Agency as it is a positional isomer of amphetamine. In this work, the development and application of a simple and rapid analytical procedure that enables discrimination between both isomers is described. The analytes of interest were extracted from urine by a two-step liquid–liquid extraction and then analyzed by UPLC/MS/MS under isocratic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 21 publications
(20 reference statements)
3
34
0
Order By: Relevance
“…Urine samples were prepared by 2 methods: dilute and shoot (DaS) and a method involving acid hydrolysis and double extraction described previously, with modification.…”
Section: Methodsmentioning
confidence: 99%
“…Urine samples were prepared by 2 methods: dilute and shoot (DaS) and a method involving acid hydrolysis and double extraction described previously, with modification.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 2.3 | Dilute-and-shoot approach Briefly, for DaS, 100 μL of urine was spiked with 5 μL of Amphetamine-D11 (internal standard) at final concentration of 500 ng/mL and diluted with 900 μL of water. 13,14 2.3 | Dilute-and-shoot approach Briefly, for DaS, 100 μL of urine was spiked with 5 μL of Amphetamine-D11 (internal standard) at final concentration of 500 ng/mL and diluted with 900 μL of water.…”
Section: Sample Preparationmentioning
confidence: 99%
“…[50] There have been reports of several cases of violations by athletes in various sporting events. [101] Four urine samples found positive for β-MePEA were used to evaluate the impact of glucuronide and sulfate deconjugation on method performance. [101] Four urine samples found positive for β-MePEA were used to evaluate the impact of glucuronide and sulfate deconjugation on method performance.…”
Section: Synthetic Phenethylamines In Dietary Supplementsmentioning
confidence: 99%
“…[99,100] Cholbinski et al reported the development and application of a simple and rapid analytical procedure for urine samples that enables discrimination between β-MePEA and amphetamine, its positional isomer. [101] This work is expected to be of significance in the area of forensic analysis of anti-doping samples because it provides a validated procedure for discriminating between amphetamine and β-MePEA. [101] This work is expected to be of significance in the area of forensic analysis of anti-doping samples because it provides a validated procedure for discriminating between amphetamine and β-MePEA.…”
Section: Synthetic Phenethylamines In Dietary Supplementsmentioning
confidence: 99%